Primary Hippocampal Cell Culture and Its Application in Medical Researches - Atik, Nur; Nandika, Alfya; Avriyanti, Erda; Bhatara, Tryando; Kartiwa, Raden Angga (Universitas Islam Bandung, 2019)
Studies in neuroscience can be performed in vitro and in vivo. In vivo studies will show significant results, but it is difficult to do and time-consuming. Primary hippocampal cell culture widely has used in neurobiological studies such as identifying the cellular mechanism of proteins, neuronal activity, and characteristics. The results of studies conducted on this cell culture will be very useful in discovering pathogenesis of a disease, the effect of a substance on the neuron, and neural basis of memory and learning. However, currently in Indonesia, primary hippocampal cell culture is still rare and difficult to do. The purpose of this study was to demonstrate that primary hippocampal cell culture can be done and developed in Indonesia and to review the application of it in medical researches. The study was an experimental study by obtaining neurons from animal’s hippocampus was conducted in 2015–2018 at Department of Cell Biology, Graduate School of Medicine Osaka University and Faculty of Medicine Universitas Padjadjaran. The experimental animal was mice embryo gathered 17.5-days postcoitus. Enzymatic and mechanical methods collected primary hippocampal cells. The cells counted and cultured, which later were observed to see neuron differentiation. The average number of culture cells from 3 embryonic’s hippocampus were 2.39×106. Neuron differentiation observed on the first day and more visible and numerous on the third day after plating. In conclusion, primary hippocampal cell culture using hippocampus from one hemisphere of embryonic mice brain showed a sufficient number of cells to carry out research and showed neuron differentiation. KULTUR SEL PRIMER HIPOKAMPUS DAN PENGGUNAANNYA DALAM RISET KEDOKTERANPenelitian dalam neurobiologi dapat dilakukan secara in vitro dan in vivo. Penelitian secara in vivo sangat berdampak hasilnya, namun sulit dan memakan waktu yang lama. Kultur sel primer hipokampus banyak digunakan dalam penelitian neurobiologi seperti melihat mekanisme protein seluler, serta aktivitas dan karakteristik neuron. Hasil penelitian yang dilakukan pada kultur sel ini akan sangat bermanfaat dalam menemukan proses suatu penyakit, efek suatu zat terhadap sel saraf, dan kemampuan belajar serta memori. Akan tetapi, saat ini di Indonesia kultur sel primer hipokampus masih jarang dan sulit dilakukan. Tujuan penelitian ini adalah menunjukkan bahwa kultur sel hipokampus primer dapat dilakukan dan dikembangkan di Indonesia, serta meninjau penerapannya dalam riset kedokteran. Penelitian ini merupakan studi eksperimental dengan mengoleksi neuron dari hipokampus hewan coba yang dilakukan pada tahun 2015–2018 di Department of Cell Biology, Graduate School of Medicine Osaka University dan Fakultas Kedokteran Universitas Padjadjaran. Hewan coba berupa embrio mencit hari ke-17,5 pascakoitus. Sel primer hipokampus dikoleksi untuk dihitung dan dikultur menggunakan metode enzimatik dan mekanik. Observasi neuron pada kultur dilanjutkan dengan mengamati diferensiasi neuron. Rerata jumlah sel kultur dari 3 hipokampus adalah 2,39×106. Diferensiasi neuron sudah tampak pada hari pertama dan makin jelas serta tampak pada hari ketiga pascapenanaman. Simpulan, kultur sel primer hipokampus menggunakan hipokampus dari salah satu sisi hemisfer otak menunjukkan jumlah sel yang cukup untuk melakukan suatu penelitian dan menunjukkan diferensiasi dari neuron.